Receptor oligomerization: from early evidence to current understanding in class B GPCRs - Ng, Stephanie Y.; Lee, Leo T.; Chow, Billy K. (Frontiers in Endocrinology, 2013)
Dimerization or oligomerization of G protein-coupled receptors (GPCRs) are known to modulate receptor functions in terms of ontogeny, ligand-oriented regulation, pharmacological diversity, signal transduction and internalization. Class B GPCRs are receptors to a family of hormones including secretin, growth hormone-releasing hormone, vasoactive intestinal polypeptide and parathyroid hormone, among others. The functional implications of receptor dimerization have extensively been studied in class A GPCRs, while less is known regarding its function in class B GPCRs. This article reviews receptor oligomerization in terms of the early evidence and the current understanding with special focus on the functional significance in class B GPCRs.